The categories of disclosure information in the annual reports - Macagnan, Clea Beatriz (2012)
This paper identifies the categories of disclosure information in the annual reports of the companies, classification like levels 1 and 2 and New Market of BM&FBovespa. The information analyze of the annual reports of the companies, corresponding to the contained exercise of 31/12/07, published and collected in June of 2008. It was verified that most of the companies presents their annual reports with clear, objective and appropriate, disclosure obligatory items of the Law no. 6.404/76 and recommended them by CVM with orientation no. 15/87. Also recognized categories of voluntary nature information, whose information portray the compromising of the companies in informing the reality of the business. That could demonstrate to the shareholders or the investors, transparency and equalitarian rights they decision, since it comes to reduce the asymmetry information among the interested parties.